Application of TOPSIS Method for Determination of the Best Dressing Parameters in Internal Cylindrical Grinding - Huong, Truong Thi Thu; Hung, Le Xuan; Trang, Nguyen Van (European Journal of Applied Sciences, 2024)
The outcomes of an investigation on establishing the best input process variables for dressing process in internal grinding SKD11 tool steel for obtaining minimal surface roughness (RS) and maximum wheel life (T) all simultaneously are given in this article. To achieve this, the multi-criteria decision-making (MCDM) problem was dealt with employing the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) techniques, and the weights of criteria were computed using the Entropy method. Furthermore, the following input factors were examined: coarse dressing depth, coarse dressing passes, fine dressing depth, fine dressing passes, non-feeding dressing, and dressing feed rate. This experiment was constructed using the Taguchi method and an L16 orthogonal array. Based on the results of the investigation, the best dressing mode for internal cylindrical grinding is being suggested.